A bibliometric analysis and literature review on emotional skills - Manjarres, María Teresa; Duarte, Diana Paola Mahecha; Navarro-Obeid, Jorge; Álvarez, Maria Laura Vergara; Martinez, Isneila; Cudris-Torres, Lorena; Hernández-Lalinde, Juan; Bermúdez, Valmore (Frontiers in Psychology, 2023)
The content, management, and implementation of social skills have been developing since the late twentieth century as a model of capabilities. For this reason, as human beings develop and train their basic cognitive and perceptual-motor functions, they increase their capacities to solve and face difficulties. This article aims to present a bibliometric and systematic review of social skills, using sources of queries in databases such as WoS and Scopus between the years 2000 and 2022, with platforms such as Bibliometrix and Gephi. Through a scientific mapping, the main authors, journals, and countries in this field were determined; likewise, the most relevant studies were classified into three categories, that is, classics, structural, and perspectives, which were represented by means of the science tree metaphor. Moreover, a program for further studies was scheduled such as in-depth qualitative research that measures in an observational and direct manner taking into consideration: emotional expressiveness, understanding emotions, regulating emotions, and behavior; the impact of social skills training in solving social problems.